Happiness and Poverty in Developing Countries A Global Perspective - Dowling, John Malcolm; Yap, Chin Fang.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book analyzes the determinants of happiness for both the rich and the poor in the developing regions of Asia, Latin America and Africa. Explanatory variables include education, health and income as well as demographic and social variables. The book highlights the overwhelming importance of health in uplifting well-being in these regions.
Keywords: Economic policy; Regional economics; Spatial economics; Development economics; Welfare economics; International economics; Emotions; Economic Policy; Regional/Spatial Science; Development Economics; Social Choice/Welfare Economics/Public Choice/Political Economy; International Economics; Emotion